Implementation of The Fisherman Insurance Premium Assistance Program (Bpan) in The Coastal Area of Kilensari Village Panarukan District, Situbondo Regency - Giyanto, Giyanto; Usrotul Hasanah; Farida Hanum (POLITICO, 2024)
This study discusses the implementation of the Fishermen's Insurance Premium Assistance Program (BPAN) in the coastal area of ​​Kilensari Village, Panarukan District, Situbondo Regency, which is based on the Decree of the Minister of Maritime Affairs and Fisheries of the Republic of Indonesia Number 31 of 2021 concerning Technical Instructions for Fishermen's Insurance Premium Assistance. The formulation of the problem in this study is how to implement the fishermen's insurance premium assistance (BPAN) in the coastal area of ​​Kilensari Village, Panarukan District, Situbondo Regency. The method used in this study is a descriptive qualitative research method. The implementation guidelines used to analyze this study are Policy Implementation Model According to Edward III (2010), namely: 1) Communication, 2) Resources, 3) Disposition, and 4) Bureaucratic Structure. The conclusion in this study shows that of the four dimensions above, only the communication dimension does not work well due to the mindset and low level of education of the fishermen themselves, while the other three dimensions can run well. The findings in this study are the existence of a solution by improving the quality of human resources (HR) for fishermen in the coastal area of ​​Kilensari Village, Panarukan District, Situbondo Regency, by providing assistance, education and training related to the implementation of the Fishermen's Insurance Premium Assistance (BPAN) program, as well as conducting continuous communication with fishermen and conducting ongoing coaching.